Pengembangan E-Modul Berbasis Flipbook dalam Model Discovery Learning untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik (Studi pada Materi Pokok Laju Reaksi) - Erniwati, Erniwati; Sudding, Sudding; Anwar, Muhammad (Program Pasca Sarjana UNM, 2022)
This development research aims to produce a flipbook-based e-module that is valid, practical, and effective. The model used is the Hannafin & Peck’s development model adapted by Tegeh which consists of a needs assessment stage, a design, and a development and implementation. The three stages involving an evaluation and revision stage. The instruments used to test the validity: e-module validation sheet, practicality test: implementation observation sheet, teacher and students’ response questionnaire and effectiveness test: motivation questionnaire and learning outcomes test. Sources of validity data were 2 expert validators, the practicality were 2 chemistry teachers and 33 students of grade XI IPA 1 at SMAN 09 Bombana as well as the effectiveness. The e-module is stated to be valid based on the validation results with an average value of 3.52 (very valid). The e-module has met the practicality criteria because the practicality test related to: (1) the implementation of the e-module with an average value of M = 1.88 (entirely conducted categories) ; (2) positive teachers’ responses 93.23%, which is (very practical criteria), and (3) positive students’ responses 88.30% (very practical criteria). E-modules are stated to be effective based on the motivation and learning outcomes of students. The increase in students' learning motivation obtained an average N-Gain in moderate category by 0.57, while the learning outcomes obtained the percentage of class completeness by 87.88%. Therefore, the results of the study indicate that the flipbook-based e-module has valid, practical, and effective qualities.